Генетичні типи докембрійських зеленокам'яних поясів - Михайлов, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
Three types of Precambrian greenstone belts — plumtectonic, permobil, and platetectonic — are separated, their properties, which are related to geodynamic conditions of the development of the Earth's crust of the Early Precambrian, are characterized, and their metallogenic significance is shown.